Canon EOS Rebel T7i/800D for dummies - King, Julie Adair (--For dummies., 2017)
Action, beauty, adventure, and art-start capturing memories today! Canon EOS Rebel T7i/800D For Dummies is your ultimate guide to taking spectacular photos-no photography experience required! The EOS Rebel offers professional features that camera phones just cannot match, and this book shows you how to take advantage of these features to take stunning photos in any situation. First, you'll take a tour of the controls to learn what everything does, where to find it, and how to use it. Next, you'll walk through the automatic, scene, and manual modes to learn the strengths and weaknesses of each, and how to choose a mode based on your goals for that particular photo. You'll learn how to capture action shots, take beautiful portraits, and get as artsy as you want to get as you adjust for color, lighting, and focus, and control exposure for different effects. Taking great photos doesn't have to be difficult! Your camera offers everything you need to perfectly capture any scene, and this book provides clear, easy-to-follow instruction to help you take full advantage of these professional tools.-Get acquainted with your camera's controls -Shoot in automatic, scene, or manual mode -Compose shots and work with lighting like a pro -Adjust for focus, color, depth of field, and more Whether you're taking pictures at a party, shooting scenery on vacation, catching action at a ball game, or just wandering around capturing spontaneous moments of beauty, awesome photos are just a few simple steps away. Your Canon EOS Rebel T7i/800D is equipped with the tools to make any scene share-worthy, and Canon EOS Rebel T7i/800D For Dummies equips you to start snapping professional-quality photos today!